History of Accounting Development - Mukhametzyanov, Rinaz Z.; Nugaev, Fatih Sh.; Muhametzyanova, Lyaisan Z. (Journal of History Culture and Art Research, 2017)
Everyone is well aware that accounting is one of the most important areas of economy, which has become so widespread in our lives today that it is impossible to imagine modern business and economy without this component. Accounting is a well thought out system that reflects the movement of various facts of economic life, no matter how different they are, and leads them into a common logical system. We can talk a lot about the features and possibilities of this science, but how often do we think about the ways this system arose, the ways of its development and becoming a separate science? During the study of this problem, an attempt was made to systematize various points of view regarding the origin and the development of accounting. After the result of the analysis, the authors identified regularities in the development of accounting and its methodical apparatus associated with the periodization of history on technological structures.